Apoptosis Versus Cell Differentiation: Role of Heat Shock Proteins HSP90, HSP70 and HSP27 - Lanneau, David (Landes Bioscience, 2007)
Heat shock proteins HSP27, HSP70 and HSP90 are molecular chaperones whose expression is increased after many different types of stress. They have a protective function helping the cell to cope with lethal conditions. The cytoprotective function of HSPs is largely explained by their anti-apoptotic function. HSPs have been shown to interact with different key apoptotic proteins. As a result, HSPs can block essentially all apoptotic pathways, most of them involving the activation of cystein proteases called caspases. Apoptosis and differentiation are physiological processes that share many common features, for instance, chromatin condensation and the activation of caspases are frequently observed. It is, therefore, not surprising that many recent reports imply HSPs in the differentiation process. This review will comment on the role of HSP90, HSP70 and HSP27 in apoptosis and cell differentiation. HSPs may determine de fate of the cells by orchestrating the decision of apoptosis versus differentiation.